CERITA RAKYAT KAMPAR “SI LANCANG”: ANALISIS FUNGSI PELAKU - Chrisna Putri Kurniati (Madah: Jurnal Bahasa dan Sastra, 2016)
The problem in this research, titled “Cerita Rakyat Kampar ‘Si Lancang’: Analisis Fungsi Pelaku” is about analysis offender. The purpose of this study was to document folklore Kampar “Si Lancang”, and describes, reveals the function of the actors in folklore Kampar Si Lancang”. The theory used Propp's theory about the functions of the perpetrators. This is a qualitative study using literature. The primary data bersumberkan Kampar folklore entitled “Si Lancang” issued by the Ministry of Education and Culture, Jakarta, 1982. The conclusion of the research is in the folklore that there are seven functions of the perpetrators.